New fluorinated poly(pyridine amide)s derived from 2, 6-bis(4-iodophenyl)-4-(4-trifluoromethylphenyl)pyridine by C–N coupling reaction. (October 2022) - Xie, Hui; Zhao, Jing-Wei; Wei, Mei-Hong; Huang, Zhi-Hui; Liu, Xiao-Ling
2, 6-Bis(4-iodophenyl)-4-(4-trifluoromethylphenyl)pyridine, as a new aromatic diiodide compound, was synthesized through a one-pot protocol by the sequential diazotization-iodination of 2, 6-bis(4-aminophenyl)-4-(4-trifluoromethylphenyl)pyridine with KI/NaNO2 / p -TsOH in acetonitrile at room temperature. A number of new aromatic fluorinated poly(pyridine amide)s containing 2, 6-diphenyl-4-(4-trifluoromethylphenyl)pyridine units were prepared via a Pd(PPh3 )2 Cl2 catalyzed carbonylation polymerization of this diiodide, diamines and carbon monoxide in DMAc in the presence of PPh3 and 1, 8-diazabicyclo[5, 4, 0]-7-undecene. These new polyamides with inherent viscosities of 0.63–0.72 dL/g were amorphous and easily soluble in amide type aprotic solvents such as NMP, DMAc, DMF and dimethyl sulfoxide at room temperature. Thermal analysis data up to 800°C in nitrogen showed their high thermal behavior with 5% weight loss temperature of 428–498°C and char yield of 62–69%. Their limiting oxygen index of 42.3–45.1 showed that the resulting poly(pyridine amide)s could be classified as "self-extinguishing polymers". Also, their thin films exhibited high optical transparency with a cut-off wavelength of 324–373 nm.